Preparation and Characterization of Kenaf Cellulosepolyethylene Glycol- Polyethylene Biocomposites - Tajeddin, Behjat (2009)
The possibility of using cellulose as natural fiber for the production of bicomposites was investigated in this study that included two stages. The first stage involved the extraction of cellulose from the cell walls of kenaf (Hibiscus cannabinus L.), an annual herbaceous crop with many environmental advantages and good mechanical properties. It was done from the bast part of the crop by chemical treatments. Then, mixture of different weights of low density polyethylene (LDPE) and high density polyethylene (HDPE), as a matrix, with the obtained cellulose, and polyethylene glycol (PEG) were blended in order to produce a biocomposite material suitable for food packaging. For the second stage, the characterization of LDPE- and HDPE-kenaf cellulose biocomposites was performed in order to develop the optimal blends with optimized thermo-mechanical properties and propensity to environmental degradation. Therefore, the mechanical properties including tensile strength, flexural and unnotched Izod Impact tests were performed using Instron Universal Testing Machine and Izod Impact Tester, respectively. Thermal properties, biodegradability and water absorption of biocomposites were investigated as well. In addition, a scanning electron microscope (SEM) was used to observe the surface morphology of the tensile fracture surface of the samples before and after biodegradation test. The results showed that the mechanical properties of the LDPE and HDPEcellulose composites decreased slightly as the cellulose content increased from 0 to 50 wt % in the biocomposite formulation. It is interesting to note that in all treatments, the mechanical behavior of biocomposites retained in an acceptable level of strength except of HDPE composites with 50% cellulose. In general, there is a good homogeneity between samples with PEG that help to find reasonable and acceptable properties. These findings were confirmed by the SEM study. Thermal analysis of composites is necessary for determining their end use. Therefore, thermal properties of biocomposites were obtained by a thermogravimetry analysis (TGA) and a differential scanning calorimetry (DSC). Addition of cellulose fillers improves the thermal resistance of these biocomposites. The results also showed that PEG has positive role in thermal behavior of composites. This finding gives a good indication that the addition of kenaf cellulose into the body of LDPE and HDPE was capable to increase their thermal degradation properties. Biodegradability of these biocomposites was performed based on soil burial test to investigate their degradation during 120 days. The findings illustrated that there is a clear trend of degradation during burial time. The degradability increased as cellulose content was raised in the composite’s formulation. Finally, water absorption was done for biocomposites. The results showed that water absorption value for both composites was higher than those of LDPE and HDPE polymers. Addition of PEG to the formulations reduced the water absorption of the composites. Generally, it seems that the results of this research may lead to a development of a new type of biocomposites using kenaf cellulose as a natural fiber that can be used to replace plastics for food packaging in the near future.